Education inequality among the Muslims in India: Historical-Present Scenario - Vikram Singh (Social Work & Society, 2023)
This paper explores the educational inequality of the Muslim community in India. It examines the socio-economic and political factors responsible for the marginalisation of the community. It covers the perceptions of education within Islam and the history of the teaching of the Muslim community in India. It tries to comprehend the challenges within the community to access education. Furthermore, it looks at the education of the Muslim community in India. Afterwards, it also explores the factors that determine the educational status of the community. Moreover, it interrogates how in the absence of government intervention, it redresses the community's backwardness; therefore, the role played by civil society organizations is very important to analyse. Hence the paper inspects the role of NGOs as social capital in the educational development of the community.